2005
DOI: 10.1038/sj.tpj.6500330
|View full text |Cite
|
Sign up to set email alerts
|

Association of cyclophosphamide pharmacokinetics to polymorphic cytochrome P450 2C19

Abstract: Cyclophosphamide (CP), a widely used cytostatic, is metabolized by polymorphic drug metabolizing enzymes particularly cytochrome P450 (CYP) enzymes. Its side effects and clinical efficacy exhibit a broad interindividual variability, which might be due to differences in pharmacokinetics. CP-kinetics were determined in 60 patients using a global and a population pharmacokinetic model considering functionally relevant polymorphisms of CYP2B6, CYP2C9, CYP2C19, CYP3A5, and GSTA1. Moreover, metabolic ratios were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 31 publications
(30 reference statements)
6
71
2
3
Order By: Relevance
“…CYP2C9*2 significantly increased CY AUC in this study, though previous reports have only shown association between CYP2B6*6 or CYP2C19*2 polymorphisms and CY PK. 46,56 These results are a bit different than the results when we just considered CY alone 57 where ALDH1A1 and CYP3A4*1B variant genotypes significantly influenced CY PK. This difference could be because of the fact that the CY PK in these results are influenced by HCY.…”
Section: Discussioncontrasting
confidence: 52%
“…CYP2C9*2 significantly increased CY AUC in this study, though previous reports have only shown association between CYP2B6*6 or CYP2C19*2 polymorphisms and CY PK. 46,56 These results are a bit different than the results when we just considered CY alone 57 where ALDH1A1 and CYP3A4*1B variant genotypes significantly influenced CY PK. This difference could be because of the fact that the CY PK in these results are influenced by HCY.…”
Section: Discussioncontrasting
confidence: 52%
“…36 In a pharmacogenetic study performed in the setting of non-Hodgkin's lymphoma treated with cyclophosphamidecontaining regimens, CYP2C19 rs4244285 has been shown to modulate cyclophosphamide conversion to active metabolites. 37 This observation, however, has not been correlated with outcome or toxicity. 37 In our study, among all SNPs involved in cyclophosphamide pharmacokinetics and including CYP2C19 rs4244285, only GSTA1 rs3957357 displayed a clinical relevance.…”
Section: Discussionmentioning
confidence: 91%
“…37 This observation, however, has not been correlated with outcome or toxicity. 37 In our study, among all SNPs involved in cyclophosphamide pharmacokinetics and including CYP2C19 rs4244285, only GSTA1 rs3957357 displayed a clinical relevance. Overall, our pharmacogenetic data indirectly suggest that detoxification of cyclophosphamide active metabolites by GSTA1 rs3957357, rather than cyclophosphamide bioactivation by CYP2C19 rs4244285, is clinically relevant in the setting of DLBCL treated with R-CHOP21.…”
Section: Discussionmentioning
confidence: 91%
“…This cytostatic agent, widely used in conditioning regimens in combination with TBI or BU, is metabolized by CYP enzymes. 3,4 It is often speculated that the broad interindividual variability of cyclophosphamide's side effects and clinical efficacy might be due to differences in pharmacokinetics. Recently, cyclophosphamide-kinetics were analyzed for functionally relevant polymorphisms of the CYP metabolizing enzymes CYP2B6, CYP2C9, CYP2C19, CYP3A5 and glutathione-S-transferase A1.…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs which are metabolized by CYP2C19 enzymes are cytostatics, proton pump inhibitors, antidepressants, sedative, beta blockers, antiviral and anti-fungal agents. [2][3][4][5][6][7][8][9] Recently, it was demonstrated that PMs of CYP2C19 showed a decrease in platelet responsiveness to clopidogrel. 10 In another study, it was reported that patients treated with antidepressants and genotyped as PMs for CYP2D6 and CYP2C19, remained in hospital for longer (median 57.5 versus 40.0 days) compared to IMs.…”
Section: Introductionmentioning
confidence: 99%